Revving up customer satisfaction: Important Performance Analysis and Customer Satisfaction Index methods in auto repair service evaluation - Nurrokhman, Agus; Jawad, Aod Abdul (Universitas Sultan Ageng Tirtayasa, 2024)
A company that repairs automotive vehicles is facing several problems regarding customer satisfaction. The aim of this research is to enhance the quality of services offered to customers. To determine customer dissatisfaction, an analysis of five quality dimensions is conducted: tangibles, reliability, responsiveness, assurance, and empathy. The methods used to improve service quality are Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The IPA method focuses on the level of importance and performance, while the CSI measures consumer satisfaction. The results of the analysis show that the level of consumer satisfaction with services, based on CSI, is 50.30%. According to the IPA method, there are six attributes in Quadrant A that require improvement: the mechanic's ability to respond quickly to customer complaints, timeliness in service, cleanliness and comfort of the facilities provided, providing fast, accurate, and satisfactory service, and the orderly arrangement of vehicle parking areas.